A chemo-mechanically coupled continuum damage-healing model for chemical reaction-based self-healing materials. (1st February 2022) - Zhang, Xiaolong; Zhu, Pingping; Zhong, Zheng
Abstract: In this paper, a chemo-mechanically coupled continuum damage-healing theory is developed for transient damage-healing problems of chemical reaction-based self-healing materials. The deformation-diffusion-chemical reaction coupling behavior and the damage-healing dynamic process of the materials are connected and unified innovatively. In line with different damage mechanisms, the damage is divided into non-chemical-reaction damage and chemical-reaction damage. The damage-healing behavior of chemical reaction-based self-healing materials is modeled as three coupling dynamic processes of damage, mass diffusion and chemical-reaction healing. Within the framework of thermodynamics, the fully coupled nonlinear constitutive relations and nonlinear damage-healing kinetic laws are formulated. And the material parameters involved in the governing equations are further specified as functions of independent variables of non-chemical-reaction damage degree, concentrations of diffusive species and extents of chemical reactions. The obtained damage-healing model is then applied to simulate the transient self-healing problem of engineering cement-based composites (ECCs) to show the model ability in fully reflecting the multi-time-scale and multi-physical-field coupling characteristics of the damage-healing process. By analyzing the self-healing mechanism and correlating the extent of precipitation reaction, the stress state, the evolutions of elastic modulus and diffusion coefficient, the stress-reaction–diffusion coupling mathematical model of self-healing ECCs is formulated. Based on this model, the transient self-healing problem of ECC thick plate with bottom constraint is numerically solved, and the transient evolution patterns of healing degree, concentration of carbonate, structural stress and elastic modulus are given. The effects of reaction rate and damage degree on the healing evolution pattern are analyzed thoroughly. The results show that the damage degree is the dominant factor affecting the healing rate and evolution pattern of ECC, and only when the damage is serious, can the healing time be significantly shortened by increasing the healing reaction rate.